PENGEMBANGAN METODE IN SILICO UNTUK KAJIAN AWAL KEAMANAN BAHAN TAMBAHAN PANGAN BARU TERHADAP RESEPTOR OPIOID - Camelia
Food additives are developed rapidly and many researches aimed to obtain new substances to be used as food additives. The food additives must be safe, thus they should not interact with some receptors in the human body that may alter pharmacological function. Hence, a new method to predict food additive interactions with certain receptors needs to be developed for preliminary study of their efficacy safety. One of the receptors is the opioid receptor. Activation of this receptor can cause addiction and respiratory depression. This research aimed to develop an in silico method for preliminary safety study of new substances as food additive candidates against opioid receptor (PDB ID: 5C1M). Geometry optimization of reference and enlisted food additives (flavouring, antioxidant, sweetener, preservative, and food colouring) was performed using Gaussian09 software with density functional theory (DFT) restricted B3LYP method. The compounds were docked to the opioid receptor using AutoDock 4.2.6 software. Food additives were ranked and clustered based on the docking results, then five top-ranking compounds from each group of food additives tested were selected to be analyzed with molecular dynamics simulation for 50 ns using Amber16 software. Interaction of food additives with the receptor and its binding affinity obtained from molecular dynamics simulation were used in this safety study. The safety prediction of food additives was based on three criteria: binding position, Ki value cut-off (1.5550×103 nM), and interactions with the key amino acids ASP147, HIS297, VAL300, dan ILE322. Out of 25 food additives, 10 compounds were predicted to be safe, 15 compounds were predicted to be potentially able to interact with the opioid receptor, and 2 compounds could not be concluded. Then, the prediction results were compared with food additive safety data from Joint FAO/WHO Expert Committee on Food Additives (JECFA). Based on the comparison, the method needs to be evaluated further before it can be used in preliminary safety study of new food additive candidates against the opioid receptor.